2013
DOI: 10.1016/j.vaccine.2012.12.076
|View full text |Cite
|
Sign up to set email alerts
|

Antigen sparing with adjuvanted inactivated polio vaccine based on Sabin strains

Abstract: Six different adjuvants, each in combination with inactivated polio vaccine (IPV) produced with attenuated Sabin strains (sIPV), were evaluated for their ability to enhance virus neutralizing antibody titers (VNTs) in the rat potency model. The increase of VNTs was on average 3-, 15-, 24-fold with adjuvants after one immunization (serotype 1, 2, and 3, respectively). Also after a boost immunization the VNTs of adjuvanted sIPV were on average another 7- 20- 27 times higher than after two inoculations of sIPV wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 29 publications
1
31
0
1
Order By: Relevance
“…Determination of the antibody titers able to neutralize wildtype poliovirus serotype 1 was outsourced to Bilthoven Biologicals and performed as previously described (21,22). In short, average virus-neutralizing (VN) antibody titers were measured after pooling of the serum samples of all rats per immunization group.…”
Section: Virus-neutralizing Antibodiesmentioning
confidence: 99%
“…Determination of the antibody titers able to neutralize wildtype poliovirus serotype 1 was outsourced to Bilthoven Biologicals and performed as previously described (21,22). In short, average virus-neutralizing (VN) antibody titers were measured after pooling of the serum samples of all rats per immunization group.…”
Section: Virus-neutralizing Antibodiesmentioning
confidence: 99%
“…Antigenic characterization of sIPV with epitope-specific monoclonal antibodies revealed that the antigenicity and stability of neutralizing epitopes during the formalin-inactivation process of sIPV are distinct from those of cIPV, and some of the epitopes may be responsible for the overall immunogenicity of sIPV. In general, the immunogenicity of type 1 sIPV is much higher than that of type 1 cIPV, but in contrast, the immunogenicity of type 2 sIPV is lower than that of type 2 cIPV in rat and mouse models [51][52][53][54][55]. For type 3, the immunogenicity is comparable between sIPV and cIPV antigens.…”
Section: Development Of Sipvsmentioning
confidence: 92%
“…Overall, clinical studies of sIPV-containing vaccines manufactured by three different institutes showed acceptable immunogenicity in humans, against three poliovirus serotypes (Sabin and wild strains), including type 2 sIPV antigen [58,[81][82][83]96], which was considered to have lower immunogenicity compared with type 2 cIPV antigen in animal models [38,39,[51][52][53][54]99]. However, it should be noted that the antigen contents of sIPV from different manufacturers cannot be directly compared by sDU, due to the current methodological difference in D-antigen ELISA assays among each institute [56].…”
Section: International Standardization Of Sipvmentioning
confidence: 99%
“…На сегодняшний день целый ряд исследовательских групп активно из-учает возможность использования различных стандартных и новых адъювантов в комбинации с вакцинами против полиовируса. Среди обычных адъювантов повышает иммуногенность гидрок-сид алюминия [121,122]. Сейчас изучаются и но-вые адъюванты, такие как эмульсии типа «масло в воде» [123] и агонисты толл-подобных рецепто-ров и других элементов неспецифичной иммунной защиты.…”
Section: новое поколение полиовакцинunclassified